“Very clever and yet too highly flavoured”: Why Robert Grierson’s History of the Canadian Presbyterian Mission in Korea and Manchuria was Unfit to Print - Glover, Frederick (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2022)
In the fall of 1921, R. P. Mackay, the secretary of the Foreign Mission Board of the Presbyterian Church in Canada (FMB), informed Dr. Robert Grierson, a pioneer of the Canadian Presbyterian Mission in Korea and Manchuria and its most talented author, that his booklet on the history of the Korean/Manchurian Mission was problematic and could not be published. Grierson’s booklet pushed the boundaries of the missionary literature genre, and, like the more radical proposals championed by missionary reformers, was considered subversive by missionary administrators. Similar to these proposals, it could have compelled a “re-thinking” of the very purposes of the missionary enterprise. It was seen as going beyond the bounds of decorum in terms of tone and content and practicality in regard to its goals. Grierson sought out a new audience — an audience in which the FMB had little interest.